Digital Media Marketing: Strategies for Success in the New Age of Advertising - AHMAD ALZUBI (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2023)
Rapid technological development has altered the traditional advertising environment, making digital media marketing an essential component of contemporary corporate strategy. The purpose of this study is to examine how to deal with the current advertising landscape and yet be successful with digital media marketing. This article offers practical advice for improving a company's digital advertising campaigns by analyzing market tendencies, customer habits, and cutting-edge technology. The research emphasizes the value of segmenting consumers, capitalizing on social media, using data-driven analytics, tailoring marketing strategies, and embracing immersive technology. Brand awareness, consumer loyalty, and long-term growth may all be improved by smart use of these tactics in today's fast-paced digital marketing landscape.